Penguatan Sistem Tata Kelola Kesehatan Berbasis Digital Guna Meningkatkan Pelayanan Kesehatan Masyarakat dan Ketahanan Sosial - Irma Gusmi Ratih; Yahdiana Harahap; Sutanto Sutanto; Prihati Pujowaskito; Faonaso Harefa; Faonaso Harefa (Faletehan Health Journal, 2026)
The development of digital technology provides significant opportunities to improve the quality of healthcare services through faster, more integrated, and data-driven systems. However, the utilization of digital technology within Indonesia’s healthcare system still faces limited digital infrastructure, suboptimal integration of health information systems, and disparities in human resource capacity, which hinder the full effectiveness of healthcare service delivery. This study aims to formulate a strategic model for strengthening digital-based health governance systems to improve the quality of public healthcare services and enhance social resilience in Indonesia. A descriptive qualitative approach was employed, involving in-depth interviews with five informants. Data were analyzed using NVivo 12 software through coding, categorization, and identification of major themes. The findings indicate that the adoption and adaptation of digital-based health governance systems play a significant role in improving healthcare service quality while simultaneously strengthening community social resilience. Adequate digital infrastructure, human resource capacity development, nationwide integration of health information systems, and strengthened interagency synergy and coordination are required to establish a more integrated, adaptive, and sustainable healthcare service system.